Wastewater irrigation and crop yield: A meta-analysis - Han-jie WANG; Jingjing WANG; Xiaohua YU (Journal of Integrative Agriculture, 2022)
Although wastewater irrigation in agriculture could be a potential adaptation to water scarcity, its effect on crop yield varies in the literature, making it difficult to evaluate its role in global food security comprehensively. Using agronomic experiment data from 62 studies between 1987 and 2021, we employ a meta-analysis to analyze the factors contributing to the heterogeneous effects of wastewater irrigation on crop yield. Our findings can be summarized as (1) the mean yield growth effect of wastewater irrigation is 19.7%; (2) domestic and breeding wastewater irrigation could significantly increase crop yield, while industrial wastewater has a negative effect although not significant; (3) high nutrients concentration of domestic wastewater is significantly positively correlated with crop yield; (4) agronomic experiment designs in terms of field experiment, experiment times, and fertilizer use could contribute to the divergent crop yield effects across the studies; (5) there is a publication bias of the research results between the English and Chinese literature; (6) the literature mainly sheds light on the short-run effect, and the long-run impact shall be an important research question in the future.